Inducible expression of A Disintegrin and Metalloproteinase 8 in chronic periodontitis and gingival epithelial cells - W. P.P. Aung (2018)
© 2016 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Background and Objectives: The expression of A Disintegrin and Metalloproteinase 8 (ADAM8) is associated with several inflammatory diseases. Elevated ADAM8 levels have been shown in gingival crevicular fluid of patients with chronic periodontitis. The objective of this study was to investigate ADAM8 expression in chronic periodontitis tissues compared with that in normal tissues. ADAM8 expression and its inductive mechanism were examined in human gingival epithelial cells (HGECs) and human gingival fibroblasts. Material and Methods: Total RNA and protein were extracted from gingival biopsies of 33 patients with chronic periodontitis and those of 23 healthy volunteers. ADAM8 mRNA and protein expression was analyzed by real-time polymerase chain reaction, immunoblotting and immunohistochemistry. ADAM8 expression in control and stimulated cells in the presence or absence of specific inhibitors for mitogen-activated protein kinase pathways was assayed by real-time polymerase chain reaction, immunoblotting, flow cytometry and immunofluorescence. Results: ADAM8 mRNA and protein expression in chronic periodontitis tissues was significantly greater than that in normal tissues (p < 0.01). Significantly increased ADAM8 expression was detected in the gingival epithelium of chronic periodontitis tissues (p < 0.001). ADAM8 mRNA expression in HGECs, but not in human gingival fibroblasts, was significantly induced by stimulation with Fusobacterium nucleatum (p < 0.05), partially via the p44/42 mitogen-activated protein kinase pathway. ADAM8 expression in the cell lysates and on the surface of HGECs was induced by stimulation with F. nucleatum. Conclusion: ADAM8 expression is increased in inflamed chronic periodontitis tissues and localized within gingival epithelium, consistent with an upregulation of ADAM8 expression in F. nucleatum-stimulated HGECs, suggesting a possible role of ADAM8 in innate immunity of periodontal tissue.